DAMPAK PANDEMI COVID-19 PADA KESIAPAN PEMBELAJARAN TADRIS MATEMATIKA IAIN METRO LAMPUNG - Loviana, Selvi; Baskara, Waskita Niti (LPPM STKIP PGRI Bandar Lampung, 2020)
Covid-19 is a virus that has spread to almost all parts of the world. This virus was confirmed to have entered Indonesian territory in March 2020. The spread of this virus caused losses not only in the economic field but also in the education sector. In the field of education, Covid-19 overhauled the Indonesian learning system, all learning activities that were originally face-to-face directly are now carried out online starting from elementary school to tertiary level. This research is a research that shows the impact of online learning activities at IAIN Metro Lampung. The data in this study are in the form of questionnaires that are distributed through Google forms links and are described qualitatively. The negative impact of Covid-19 students' understanding of the material is deemed to be less than optimal and lecturers are less able to conduct a comprehensive assessment of students so learning is less effective. The positive impact of Covid-19 students can master the online learning platform used by lecturers so that they are ready to become teachers who are able to face the demands of the industrial era 4.0. The subjects consisted of all Tadris Mathematics students at IAIN Metro Lampung.